GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP SEMANGAT KERJA SERTA DAMPAKNYA PADA KINERJA PEGAWAI DI KANTOR PANWASLU SE- KECAMATAN KABUPATEN OKU - Emelda Emelda (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2020)
The problem in this study, first is whether there is an influence of leadership style and compensation together or partially on morale. Second, whether there is an influence of leadership style, compensation and work spirit together or partially on employee performance. This study aims to find answers to the problem formulation. The design of this study uses a quantitative approach that is associative. This study will explain the relationship of influencing and influenced by the variables to be examined, namely the influence of leadership style and compensation to work morale and its impact on employee performance and does not violate the law, morals, and ethics. The population was 130 respondents, which were sampled in this study were 99 respondents to represent the population of OKU District Panwaslu staff. The sampling technique used in this study is the simple random sampling technique, which is the research sample taken using simple random methods. Analyzing the data in this study used path analysis techniques (path analysis). The results of this study concluded the first positive and significant influence of leadership style and compensation together or partially on work morale. Second, there is a positive and significant influence of leadership style, compensation and working spirit together or partially on the performance of employees in the Oversight Panwaslu Office in OKU Regency. Researchers still suggest that the Panwaslu leadership should pay attention to compensation, encouragement and motivation so that employee performance increases